1987
DOI: 10.1007/bf01042044
|View full text |Cite
|
Sign up to set email alerts
|

Arsen-Gehalt in einigen spanischen Weinen. Beeinflussung des Arsengehaltes von Most und Weinen durch kellertechnische Ma�nahmen

Abstract: All of the essential technological means of treating grapes, must and wine were examined systematically. The main reasons for the differences in the arsenic (As) content of rosé and red wines are explained. In this study a relationship has been found between the As level and the wine-making technique. Rosé wines contain more As than red wines because they require a shorter period of contact with the skins. In order to prove this, the average values for the rosé and red wine samples from the same winery were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 8 publications
2
28
0
Order By: Relevance
“…The mean arsenic content of red wines was found to be significantly lower than that of rosé and white wines (Barbaste et al 2003). These differences can be due to the different methods of vinification (Aguilar et al 1987).…”
Section: Arsenicmentioning
confidence: 99%
“…The mean arsenic content of red wines was found to be significantly lower than that of rosé and white wines (Barbaste et al 2003). These differences can be due to the different methods of vinification (Aguilar et al 1987).…”
Section: Arsenicmentioning
confidence: 99%
“…Red wines showed a higher As content than white wines, which can be explained by the more intensive extraction processes from the turbid and solid fractions, whereas differences before and after malolactic fermentation were not noted, suggesting negligible bioabsorption phenomena on bacteria. Aguilar et al [20] observed a higher content of As in white wines, but this inconsistency is probably due to the different protocols followed during winemaking, particularly regarding the use of bentonite, pressing, and contact with juice lees, because As is also present in significant amounts in the skin of the berry [14].…”
Section: Arsenic In Winesmentioning
confidence: 99%
“…The total As content increases progressively in the berry as it develops and matures; at ripe-ness, the element is localized mainly in the pulp and skin with only approximately 10% in the seeds [14]. Arsenic concentration in wine generally varies from <0.5 to 17 mg/L [15][16][17][18][19], with higher concentrations in white wine [20]. Some oenological treatments, such as the use of bentonite and fossil shell flour, are also reputed to affect the final concentration of As in wine [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Once stratified by wine type, white wine had a higher concentration of Pb than red wine. It has been suggested that yeast present in grape skins binds heavy metals and may remove these elements from the aqueous solution (Aguilar et al 1987). This may explain the observed reduction of Pb content in red wine, due to its extended length of contact with grape skins during the fermentation process.…”
Section: Pb Content By Wine Typementioning
confidence: 99%